2010
DOI: 10.1007/s00726-010-0732-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of taurine homeostasis by protein kinase CK2 in mouse fibroblasts

Abstract: Increased expression of the ubiquitous serine/threonine protein kinase CK2 has been associated with increased proliferative capacity and increased resistance towards apoptosis. Taurine is the primary organic osmolyte involved in cell volume control in mammalian cells, and shift in cell volume is a critical step in cell proliferation, differentiation and induction of apoptosis. In the present study, we use mouse NIH3T3 fibroblasts and Ehrlich Lettré ascites tumour cells with different CK2 expression levels. Tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Furthermore, inhibition of CK2 also results in decreased activity of the swelling induced taurine release pathway (Fig. 2) [18]. As the effect of CK2 inhibition on taurine transport was similar in the two cell lines it was suggested that CK2 suppresses taurine accumulation regardless to the CK2 expression level.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, inhibition of CK2 also results in decreased activity of the swelling induced taurine release pathway (Fig. 2) [18]. As the effect of CK2 inhibition on taurine transport was similar in the two cell lines it was suggested that CK2 suppresses taurine accumulation regardless to the CK2 expression level.…”
Section: Introductionmentioning
confidence: 88%
“…Previous reports have introduced the serine/threonine kinase CK2 as a regulator of the active taurine uptake and the passive taurine release [18,19]. CK2 is constitutively active and upregulated in most types of cancers as well as growth stimulated cells where it stimulates proliferation and suppresses apoptosis [20] (see [21]).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular taurine content is generally a balance between active uptake via the Na ϩ -and Cl Ϫ -dependent taurine transporter (TauT), passive release via volume-sensitive and volume-insensitive transporters (28), and in some cells (liver, pancreas, and testis) synthesis from cystein/methionine (31). Acute modulation of TauT activity involves Ser/Thr kinases (PKA, PKC, and CK2) and reactive oxygen species (ROS) (12,13,22,31,40,41,63), whereas long-term regulation of TauT activity involves transcriptional regulation by cellular osmo-sensing proteins (TonEBP, tonicity end-binding protein) and amino-sensing kinases (mTOR, mammalian target of rapamycin) (9,27,30,31). In contrast to the active taurine uptake system involving TauT, taurine release involves 1) volume-sensitive leak pathways, activated by osmotic cell swelling [termed the volumesensitive organic anion channel (VSOAC)]; and 2) volumeinsensitive leak pathways, activated during anoxia, apoptosis, and cholesterol depletion (27,31,45,61).…”
mentioning
confidence: 99%
“…The total body pool is controlled by renal taurine retention via TauT located at the proximal tubule and distal nephron. Translocation of one taurine molecule across the plasma membrane via TauT involves two to three Na ions and acute modulation of TauT activity by protein kinases (PKA, PKC, CK2) and ROS involves shift in TauT's substrate affinity, transport capacity, and/or the Na:taurine stoichiometry (13,14,19,45,69). Passive taurine release from cells via VSOAC activation involves 1) mobilization of arachidonic acid from the nuclear envelope by cell-specific PLA 2 subtypes (52,53), ROS generation by NADPH oxidases (8,34), and fatty acid oxidation to leukotrienes by 5-lipoxygenase (5-LO) (38); 2) increased tyrosine kinase activity (34,51); and 3) activation of protein kinases normally related to growth factor signaling, i.e., phosphatidylinositol 3-kinase (PI3K), Akt, and glycogen synthase kinase 3␤ (GSK3␤) (36).…”
mentioning
confidence: 99%